Whey Protein–Quercetin–Gellan Gum Complexes Prepared Using pH-Shift Treatment: Structural and Functional Properties - Na Guo; Xin Zhou; Ganghua Zhou; Yimeng Zhang; Guoqing Yu; Yangliu Liu; Beibei Li; Fangyan Zhang; Guilan Zhu (Foods)
The objectives of this study were to prepare whey protein–quercetin–gellan gum conjugates using the pH-shift method and to evaluate the impacts of varying pH values and quercetin concentrations on the interaction mechanisms and functional characteristics of the complexes. Spectroscopic analyses (fluorescence, UV-vis, and FT-IR) revealed that new complexes formed under alkaline conditions. Notably, an increasing quercetin concentration led to a reduction in complex particle size and an increase in the zeta potential value, with these effects being more pronounced under alkaline conditions. The particle size was 425.7 nm, and the zeta potential value was −30.00 mV at a quercetin addition concentration of 15 umol/g protein. Additionally, the complexes formed under alkaline conditions exhibited superior foaming capacity, emulsification properties, and significantly enhanced free radical scavenging activity. The complex’s DPPH and ABTS radical scavenging rates rose by 41.57% and 57.69%, respectively. This study provides theoretical foundations and practical insights for developing protein—polyphenol systems, offering significant implications for the application of quercetin functional foods and supplements in the food science and pharmaceutical industries.